Edugame Development: Genius Learn Platformer to Increase Students' Learning Motivation and Learning Outcomes - Yusuf, Ahmad; Hardianto, Deni (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to develop and test the effectiveness of the “Platformer Genius Learn” edugame to improve students’ motivation and learning outcomes in the Fundamentals of Educational Technology course using the ADDIE development model. This limited trial subject consisted of one class with a total of 26 subjects who were first-semester students of the Educational Technology Study Program at Padang State University. The tools used in this study included validation sheets for subject matter experts and media experts, student learning motivation questionnaires, and pre-test and post-test assessments to measure the results.The results of the study show: 1) edugame: Platformer Genius Learn Suitable for use based on media expert validation showing an average score of 4.13 in the "Valid" category and the validation of a subject matter expert with an average score of 4.25 in the "Highly valid" category; 2) practicality of Edugame: Platformer Genius Learn at one to one trial obtained an average of 3.13 in the category of "quite practical", small group trial obtained an average of 4.03 in the "practical" category, and field trial obtained an average of 4.51 in the category of "very practical"; and 3) edugame effectiveness: Platformer Genius Learn proven through test analysis Paired Sample t-test show a significant improvement in student learning outcomes after using edugame media, and the results of the N-Gain Score calculation showed a value of 0.75, which is included in the high category. In addition, the results of the learning motivation questionnaire also show an average of 4.53, categorised as "very appropriate". Thus, Edugame Media: Platformer Genius Learn has been declared effective as an innovative, interactive learning medium that enhances learning motivation and outcomes among students in the Educational Technology Study Program at the State University of Padang.